Visitors’ dining experience and their behavioural intention towards restaurants in Bandar Diraja Muar, Johor - Rahim, Nur Elina Syafiqah; Md Sawari, Siti Salwa (2019)
Many advertisements and reviews on the varieties of food in Malaysia specifically in Bandar Diraja Muar which is located in Johor. However, there are still few research that have been done about the study of tourists’ experience and the service of restaurants in Muar. Therefore, the purpose of this paper is to study the dining experience of visitors and their behavioural intention towards the restaurants in Muar. This study is focused on the restaurants in Muar as the study area. A set of questionnaire is used for data collection and distributed to visitors who have experienced the food and its services in Muar. This study also used IBM SPSS to perform the analysis of the data by engaging descriptive analysis and inferential statistics. The findings of this study portrayed the quality of food in the restaurants, and the visitors’ behavioural intention based on their experience and the services that they received. Also, the research has found that there is significant relationship between visitors dining experience and their behavioural intention based on their experience and the services towards the restaurants in Muar. This contribution of this study will help the business industry of food providers in Muar to be more acknowledge and boost visitors’ behavioural intention and thus the well-known Muar as a food heaven is well-known.